Freddie and the fairy - Donaldson, Julia (Macmillan Publishers Limited, 2010)
Freddie is delighted when he meets a fairy who offers to grant his every wish.But bessie-belle can't hear very well,and all freddie's wishes come out wrong.whatever can they do?
Keywords: Fairytales